Genotoxic bystander signals from irradiated human mesenchymal stromal cells mainly localize in the 10-100 kDa fraction of conditioned medium - Samra, Vanessa; Fabarius, Alice; Drews, Oliver; Bierbaum, Miriam; Jawhar, Ahmed; Darwich, Ali; Weiß, Christel; Flach, Johanna; Brendel, Susanne; Kleiner, Helga; Seifarth, Wolfgang; Hofmann, Wolf-Karsten; et al. (Cells, 2021)
Genotoxic bystander signals released from irradiated human mesenchymal stromal cells (MSC) may induce radiation-induced bystander effects (RIBEs) in human hematopoietic stem and progenitor cells (HSPC), potentially causing leukemic transformation. Although the source of bystander signals is evident, the identification and characterization of these signals is challenging. Here, RIBEs were analyzed in human CD34+ cells cultured in distinct molecular size fractions of medium, conditioned by 2 Gy irradiated human MSC. Specifically, γH2AX foci (as a marker of DNA double-strand breaks) and chromosomal instability were evaluated in CD34+ cells grown in approximate (I) < 10 kDa, (II) 10-100 kDa and (III) > 100 kDa fractions of MSC conditioned medium and un-/fractionated control medium, respectively. Hitherto, significantly increased numbers of γH2AX foci (p = 0.0286) and aberrant metaphases (p = 0.0022) were detected in CD34+ cells grown in the (II) 10-100 kDa fraction (0.67 ± 0.10 γH2AX foci per CD34+ cell ∨ 3.8 ± 0.3 aberrant metaphases per CD34+ cell sample; mean ± SEM) when compared to (I) < 10 kDa (0.19 ± 0.01 ∨ 0.3 ± 0.2) or (III) > 100 kDa fractions (0.23 ± 0.04 ∨ 0.4 ± 0.4) or un-/fractionated control medium (0.12 ± 0.01 ∨ 0.1 ± 0.1). Furthermore, RIBEs disappeared after heat inactivation of medium at 75 °C. Taken together, our data suggest that RIBEs are mainly mediated by the heat-sensitive (II) 10-100 kDa fraction of MSC conditioned medium. We postulate proteins as RIBE mediators and in-depth proteome analyses to identify key bystander signals, which define targets for the development of next-generation anti-leukemic drugs.
Gesehen am 28.07.2021